GDPR AND CHALLENGES OF PERSONAL DATA PROTECTION - Žaklina; Vicentijevic, Kosana (The European Journal of Applied Economics, 2022)
The paper discusses the challenges of implementing GDPR regulation in the EU and the Republic of Serbia. The regulations governing the issue of personal data protection are outlined. Emphasis is placed on reconciling this issue in the Republic of Serbia with EU legislation. The aim of this paper is to look at GDPR regulations from several aspects of the business of taxpayers. It is necessary to include all segments of the business entity in the implementation of this regulation, as well as bodies at the national level. It is necessary to adopt by-laws in order to fully implement the Law on Personal Data Protection in the Republic of Serbia.